Preparation and characterization of PEO-PMMA-LiCIO[4]-EC-MnO[2] nanocomposite polymer electrolytes / Tan Say Min - Tan, Say Min (2012)
Polymer electrolytes are of great interest for solid-state-electrochemical devices especially in fuel cells and battery. There have been many studies that carried out to improve the ionic conductivity in polymer electrolytes which include polymer blending, incorporating plasticizers and filler additives in the electrolytes system. This thesis describes the combined effect of incorporating the nano-sized MnO2 filler and the EC plasticizer on the ionic conductivity enhancement of the polymer blend PMMAPEO- LiClO4 electrolyte. Maximum conductivity has been achieved by optimizing the compositions of the plasticizer and the filler. Conduction characteristics of the polymer electrolyte system are investigated. Free standing flexible electrolyte films of composition 13.68 wt% PEO, 54.72 wt% PMMA, 7.59 wt% LiClO4, 19 wt% EC and 5 wt% MnO2 are prepared by solution casting method. A combination of X-ray diffraction (XRD), UV-Vis spectroscopy, Fourier-transform infrared (FTIR) spectroscopy, Field Emission Scanning Electron Microscopy (FESEM), thermal gravimetric analysis (TGA) and differential scanning calorimetry (DSC) studies have indicated enhancement in the amorphous phase of polymer system due to the polymer blend, plasticizer addition and filler addition. Further, a reduction in the glass transition temperature and optical band gap has inferred increase in the flexibility of the polymer chains. Ionic conductivity studies are carried out as a function of chemical composition and temperature using impedance spectroscopy. The conductivity values are presented and results are discussed.